FUNGSI PEMBINAAN PEMERINTAHAN KEPENGHULUAN TERHADAP LEMBAGA KEMASYARAKATAN KEPENGHULUAN DI KEPENGHULUAN BAGAN NIBUNG KECAMATAN SIMPANG KANAN KABUPATEN ROKAN HILIR TAHUN 2015-2016 - Nurhazizah "; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The Government of Village has the authority to supervise the existing social institutions in every kepenghuluan, the guidance done by the introduction of duties and functions of every institution namely the institution of PKK and the RW . This study aims to find out the guidance of government kepenghuluan to community institutions in Village Bagan Nibung District Simpang Kanan Kistrict RokanHilir.This research uses qualitative research method with descriptive research type, which can be interpreted as problem solving process investigated by describing the state of research subject based on facts that appear during the research which then proceed with based on existing theories. Development of government kepenghuluan in conducting coaching has not run maximally, government kepenghuluan only provide guidance about the main task and function, Because so far there is no coaching from local government so that institution in carrying out duty and function not yet fully reached.Based on the results of research that has been done on the function of fostering governance kepenghuluan to community institutions kepenghuluan in kepenghuluan Bagan Nibung Simpang Kanan District Rokan Hilir District 2015-2015 researchers can conclude that, the guidance is do by government kepenghuluan to community institutions less maximum so that community institutions especially PKK And RW has not done its job well. Should the local government should provide guidance to the government kepenghuluan about community institutions such as training so that coaching conducted by the government Village should run optimally. Obstacles faced by the government village and community institutions in carrying out activities namely, working conditions, skills and human resources.Keywords: Guidance, Governmental Affairs, Community Institutions